Determinan Penangguran Usia Muda di Wilayah Perkotaan Tahun 2016-2019 - Sisca Gustina Sari (Journal of Economics and Business Aseanomics (JEBA), 2020)
The economic development of a country can be seen from indicators open unemployment rate that are able to show the state of the population's income distribution and know who benefits from economic development. From 2016-2019, young people have always been the highest contributor to Indonesia's open unemployment rate. This study discusses the factors that influence the open unemployment rate of urban youth in Indonesia in 2016-2019. The factors are population growth rate, expenditure per capita population, average length of schooling, youth working with high school graduates, provincial minimum wages, registered job seekers and foreign investment. This study uses the panel data linear regression method with the Random Effect Model. The results show that the rate of population growth and foreign investment has a significant positive effect, expenditure per capita of the population and registered job seekers has a significant negative effect, youth working based on the highest education completed are Secondary school and provincial minimum wages have a significant positive effect, the average length of schooling has a negative and insignificant effect